THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE FINANCIAL PERFORMANCE OF SHARIA PUBLIC BANK INDONESIA IN 2019-2021 - Andriani Andriani; Della Rohmatul Fauziah (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2023)
The increasing market share of Islamic banking makes competition between Islamic banks tighter. The increasing competition of Islamic banks can be overcome by improving their financial performance. Intellectual capital as one of the intangible resources is considered to have an influence on improving financial performance for Islamic banks. This study aims to determine the value of intellectual capital and the level of financial performance of Islamic commercial banks in Indonesia, as well as the effect of intellectual capital on the financial performance of Islamic commercial banks in Indonesia. The method used in this research is quantitative with secondary data sources. The sample technique is in the form of purposive sampling with a total n of 84 and using simple linear analysis. The results of the study indicate that there is a positive influence of intellectual capital on the financial performance of Islamic commercial banks in Indonesia.